A novel process for manufacturing large-diameter thin-walled metal ring: Double-roll pendulum hot rotary forging technology. (April 2022) - Chen, Mingchao; Zhu, Chundong; Yu, Zhongquan; Ma, Chong
Abstract: Large-scale thin-walled metal ring parts are the key main structural parts in new energy sources and aerospace equipment. How to form reliable large-diameter thin-walled metal rings has become the focus of attention of researchers. This paper proposes a double-roll pendulum hot rotary forging (DRPHRF) process for forming such components and demonstrates the feasibility of forming rings with a diameter of 4 m and a thickness of 0.1 m (axial) using this process. The forming process of DRPHRF is analyzed and designed, and the critical instability and forming conditions are obtained. The finite element model of the ring DRPHRF was established in the DEFORM-3D software using the scale-down process with a ratio of 10:1, and the accuracy of the model was verified through experiments. Based on the reliable finite element model, the deformation behavior of the ring DRPHRF is analyzed. The results show that each part of the ring is subjected to periodic stress, which reduces the residual stress. The uniform circumferential equivalent plastic strain (PEEQ) distribution and the characteristics that the axial PEEQ becomes uniform as the thickness decreases are conducive to forming a thin-walled ring with uniform performance. There is less heat loss during the forming process, which is beneficial to reduce the stress during forming. Highlights: Propose the double-roll pendulum hot rotary forging process to produce a metal ring with a diameter of 4 m and a thickness of 0.1 m. The stability of the ring processing and the forming conditions are obtained, and the scale-down process with a ratio of 10 is used to establish and experimentally verify the finite element. The results suggest that the smaller the ring height H and the angle, the larger the r and R, the more unstable the ring. Stress history, strain distribution and temperature evolution are all conducive to forming large thin-walled rings.